The 2008 Nura earthquake sequence at the Pamir‐Tian Shan collision zone, southern Kyrgyzstan. Issue 12 (5th December 2014) - Sippl, C.; Ratschbacher, L.; Schurr, B.; Krumbiegel, C.; Rui, H.; Pingren, L.; Abdybachaev, U.
Abstract We analyzed the 5 October 2008, Mw 6.6 Nura earthquake, which occurred in the border triangle between Kyrgyzstan, Tajikistan, and China, and its aftershock series based on locally recorded seismic data. More than 3000 aftershocks were detected and located, using a double‐difference technique and a regional 3‐D velocity model. Moment tensors for the main event and the 42 largest aftershocks were determined by full‐waveform inversion of long‐period displacement seismograms. The Nura main shock was a shallow (∼3.4 km deep) reverse faulting event and occurred on an approximately east striking rupture plane situated east of the Alai Valley, along the Pamir Frontal Thrust of the Trans Alai Range, the leading edge of the Pamir Thrust System. Its presumed rupture plane dips steeply (∼59°) southward. The aftershocks constitute several distinct clusters that can be attributed to the activation of an array of individual faults including the one that was presumably broken by the main shock. Background seismicity occurred mainly further south, behind the crest of the Trans Alai Range, in an approximately east trending zone of dextral transpressional motion in the interior of the Pamir Thrust System. We show that nearly all reactivated structures lie in regions that experienced an increase in Coulomb stress due to the main shock rupture. The Nura earthquake sequence indicates slip partitioning between north‐south shortening that creates large earthquakes along the Pamir Frontal Thrust, and lateral movement in the interior of the Pamir Thrust System.